Short-Term Exposure to Sterile Seawater Reduces Bacterial Community Diversity in the Sea Anemone, Exaiptasia diaphana - Dungan, Ashley M.; van Oppen, Madeleine J. H.; Blackall, Linda L. (Frontiers in Marine Science, 2021)
The global decline of coral reefs heightens the need to understand how corals may persist under changing environmental conditions. Restructuring of the coral-associated bacterial community, either through natural or assisted strategies, has been suggested as a means of adaptation to climate change. A low complexity microbial system would facilitate testing the efficacy of microbial restructuring strategies. We used the model organism for corals, Exaiptasia diaphana, and determined that short-term (three weeks) exposure to filter-sterilised seawater conditions alone reduced the complexity of the microbiome. Metabarcoding of the V5-V6 region of the bacterial 16S rRNA gene revealed that alpha diversity was approximately halved in anemones reared in filter-sterilized seawater compared to controls reared in unfiltered seawater and that the composition (beta diversity) differed significantly between the two. By reducing the complexity of the E. diaphana microbiome, the development of a system for testing assisted strategies such as probiotics, is more feasible.